145 Prognostic value of three-dimensional echocardiographic assessment of tricuspid valve geometry in atrial and ventricular functional tricuspid regurgitation. (8th December 2021) - Heilbron, Francesca; Gavazzoni, Mara; Florescu, Diana; Ochoa, Roberto; Tomaselli, Michele; Cascella, Andrea; Ciampi, Pellegrino; Rella, Valeria; Volpato, Valentina; Oliverio, Giorgio; Ciambellotti, Francesca; Branzi, Giovanna; et al.
Abstract: Aims: Atrial and ventricular functional tricuspid regurgitation (A-FTR and V-FTR) have recently emerged as different phenotypes of FTR. Given the difference in mechanisms that are postulated to be underlying these two entities, a different remodelling of tricuspid valve (TV) apparatus can occur and therefore also a specific quantitative approach could be deemed. Moreover, considered the known limitation of the two-dimensional flow convergence method (2D-PISA) for quantifying FTR in advanced valve apparatus remodelling with irregular effective valve orifice (ERO) morphology, it would be expected that also the parameters of severity of FTR can be different in these two types of FTR. The aim of this study was to investigate the TV apparatus remodelling in the two different phenotypes of FTR: ventricular (V-FTR) and atrial (A-FTR) and the role of echocardiographic parameters of TV remodelling and TR severity to predict clinical outcomes. Methods and results: The present retrospective study included consecutive patients with moderate to severe functional tricuspid regurgitation (FTR) referred for echocardiography in two Italian centres. The composite endpoint of death for any cause and heart failure (HF) hospitalization was used as primary outcome of this analysis. According to more recent guidelines, patients were considered having A-FTR if having history of long-standing atrial fibrillation, without history of pulmonary hypertension and left side heart disease. A total of 180 patients were included. Despite the right atrial volume (RAV) was not different in the two groups, in A-FTR tethering height was significantly lower (11.7 ± 4.8 mm vs. 15.0 ± 5.5 in V-FTR. P < 0.01) and the 3D-derived tricuspid annulus (TA) diameters were larger both in end-diastolic and mid-systolic phase (3D-TA-End diastolic-major axis: 45.2 ± 6.2 mm in A-FTR vs. 42.8 ± 5.4 in V-FTR. P = 0.04; 3D-TA mid systolic major axis: 41.7 ± 6.4 mm in A-FTR vs. 37.9 ± 5.1 in V-FTR, P < 0.01). 3D-TA-End diastolic-minor axis: 39.7 ± 6.8 vs. 37.1 ± 5.2. P = 0.03. Regarding the parameters of severity of FTR, patients with V-FTR had larger vena contracta (VC), either when 2D estimated or 3D (2D-VC-average: 5.3 ± 2.8 mm in A-FTR vs. 6.6 ± 3.7 in V-FTR. P = 0.02; 3D-VCA: 0.9 ± 0.4 cm 2 vs. 1.3 ± 1.1 cm 2, P = 0.02); conversely the value of 2D-ERO and regurgitant volume estimated with 2D-PISA method did not show significant difference between the two groups. After a median follow-up of 24 months (IQR: 2–48) 72 patients (40%) reached the primary endpoint and 64 (36%) hospitalized for HF. Different predictors of combined endpoint were found in the two groups: tenting height. 2D-VC. 3D-VCA and regurgitant fraction were prognostic correlates in V-FTR; TA dimensions as well as all the parameters of severe TR, including EROA with PISA method were related to the prognosis in A-FTR. Conclusions: Different TV remodelling occurs in patients with A- and V-FTR, having the second more pronounce tethering of TV leaflets; the prognostic role of quantitative parameters of FTR in these two groups is different, thus reaffirming: (1) the limitation of PISA method without correction in case of more pronounced tenting of leaflets; (2) the difference in underlying pathogenic mechanisms; and (3) the needing for a more specific diagnostic approach and prognostic stratification in these two FTR phenotypes.